2021
DOI: 10.3390/biomedicines9081039
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 Overexpression Triggers PINK1-IP3R-Mediated Neuroprotective Mitophagy

Abstract: An experimental model of spinal root avulsion (RA) is useful to study causal molecular programs that drive retrograde neurodegeneration after neuron-target disconnection. This neurodegenerative process shares common characteristics with neuronal disease-related processes such as the presence of endoplasmic reticulum (ER) stress and autophagy flux blockage. We previously found that the overexpression of GRP78 promoted motoneuronal neuroprotection after RA. After that, we aimed to unravel the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…GRP78 also maintains mitochondrial functionality by reducing Ca 2+ efflux from the ER to mitochondria and by managing misfolded mitochondrial proteins and mitochondrial steroidogenesis [49][50][51]. Recently, it has been proposed that GRP78 overexpression aids neuroprotection by triggering the mitophagy process [52]. Our real-time PCR and western blotting results confirm that GRP78 activity is higher in B16F1 cells than mouse 3T3-Swiss albino cells (Fig.…”
Section: Formation Of the Apoptotic Bodies Confirm Cellular Apoptosis...supporting
confidence: 78%
“…GRP78 also maintains mitochondrial functionality by reducing Ca 2+ efflux from the ER to mitochondria and by managing misfolded mitochondrial proteins and mitochondrial steroidogenesis [49][50][51]. Recently, it has been proposed that GRP78 overexpression aids neuroprotection by triggering the mitophagy process [52]. Our real-time PCR and western blotting results confirm that GRP78 activity is higher in B16F1 cells than mouse 3T3-Swiss albino cells (Fig.…”
Section: Formation Of the Apoptotic Bodies Confirm Cellular Apoptosis...supporting
confidence: 78%
“…In addition, GRP78 has been shown to bind ions of Са 2+ , by blocking the activation of ER‐associated proapoptotic factors, such as BIK and caspase‐7 36 . There is an evidence of neuroprotective properties of the GRP78 protein 37 . In this study, a much higher level of GRP78 expression was observed in the hypothermia group than in the normothermic ischaemia/reperfusion group.…”
Section: Discussion/conclusionmentioning
confidence: 48%
“…36 There is an evidence of neuroprotective properties of the GRP78 protein. 37 In this study, a much higher level of GRP78 expression was observed in the hypothermia group than in the normothermic ischaemia/reperfusion group. This may indicate that GRP78 expression is facilitated by hypothermia-induced neuroprotection in the hippocampal region during cerebral ischaemia/reperfusion.…”
Section: The Expression Of Grp78 P-perk P-eif2α Atf4 and Chopmentioning
confidence: 45%
“…The latter hypothesis lacks a clear definition in ischemic stroke and the roles of mitophagy in cerebral ischemia may vary across experimental models ( Table 1 ). In fact, previous studies propose that different compounds or gene manipulations confer neuroprotection with reduced mitophagy in ischemic brains [ 65 , 66 , 85 ]. Bnip3 knockout attenuates ischemic brain injury and mitophagy induction [ 12 ], but the gene plays a more complex role in regulating apoptosis and lysosomal function [ 86 , 87 ].…”
Section: Reviewmentioning
confidence: 99%